CHAVE DE IDENTIFICAÇÃO INTERATIVA PARA OS PHLEBOTOMINAE (DIPTERA, PSYHODIDAE) DO ESTADO DE SÃO PAULO, BRASIL - Shimabukuro, P.H.F; Galati, E.A.B.; Tolezano, J.E.; Carvalheiro, J.R. (Revista do Instituto Adolfo Lutz, 2006)
Ver PDF.